Effects of surfactants on the molecular aggregation of squaraine dye Sq-2Me in aqueous solutions - Yefimova, S.L.; Guralchuk, G.Ya.; Lebed', A.S.; Sorokin, A.V.; Malyukin, Yu.V.; Kurilchenko, I.Yu. (Functional Materials, 2009)
The influence of anionic surfactant, sodium dodecyl sulphate (SDS), and cationic one, cetylpyridinium bromide (CPB), on aggregation behavior of squaraine dye Sq-2Me has been studied in aqueous solutions by optical spectroscopy. It has been found that the addition of surfactants at concentrations higher than critical micelle one CIIJ,TcyTeK<lJemr:u.T into a DMF-W (95 %) solution does not prevent the dye aggregation. The structure of Sq-2Me aggregates formed in SDS and CPB micelles is discussed using the exciton theory. The results show that the optical properties and the Sq-2Me aggregate structure can be tuned using interaction with surfactant micelles of different nature.